2009
DOI: 10.1007/s00438-009-0464-4
|View full text |Cite
|
Sign up to set email alerts
|

Mapping SNP-anchored genes using high-resolution melting analysis in almond

Abstract: Peach and almond have been considered as model species for the family Rosaceae and other woody plants. Consequently, mapping and characterisation of genes in these species has important implications. High-resolution melting (HRM) analysis is a recent development in the detection of SNPs and other markers, and proved to be an efficient and cost-effective approach. In this study, we aimed to map genes corresponding to known proteins in other species using the HRM approach. Prunus unigenes were searched and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 45 publications
(33 reference statements)
0
26
0
3
Order By: Relevance
“…HRM profiles of the fragments and evaluation techniques were established and the resulting SNP data were used to cluster the accessions of wild almond species. HRM is a novel, homogenous and closed-tube post-PCR method that can be applied to analyse the genetic variations as well as SNPs, polymorphism length and methylations of DNA in PCR amplicons 40, 41 . HRM requires an additional step, the melting process following cycling, and an additional reagent, a specific generic DNA fluorescence dye, to complete the assay compared to conventional PCR.…”
Section: Discussionmentioning
confidence: 99%
“…HRM profiles of the fragments and evaluation techniques were established and the resulting SNP data were used to cluster the accessions of wild almond species. HRM is a novel, homogenous and closed-tube post-PCR method that can be applied to analyse the genetic variations as well as SNPs, polymorphism length and methylations of DNA in PCR amplicons 40, 41 . HRM requires an additional step, the melting process following cycling, and an additional reagent, a specific generic DNA fluorescence dye, to complete the assay compared to conventional PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Because of these benefits, HRM has already been used in many investigations including the detection of SNP mutations (Margraf et al 2006;Wu et al 2008), RNA editing (Chateigner-Boutin and Small 2007), identification of transgenic plants (Akiyama et al 2009), varietal identification (Mackay et al 2008), and food traceability (Ganopoulos et al 2010;Jaakola et al 2010). HRM analysis has also been successfully used for genetic mapping in white lupin, barley, apple, and almond (Chagné et al 2008;Croxford et al 2008;Lehmensiek et al 2008;Wu et al 2009). It has also been used to develop a genetic map of SNP markers in Cryptomeria japonica (Ujino-Ihara et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…More recently, Bielsa et al (2014) used SNP markers to characterize different Prunus rootstocks. In almond, Wu et al (2009) andTavassolian et al (2010) created the first genetic maps combining SNP markers with other markers, including RAPDs and SSRs. Later, Eduardo et al (2013) and Martínez-García et al (2013a, b) identified the first SNPs linked to quantitative trait loci (QTL) in highly saturated peach linkage maps.…”
Section: Introductionmentioning
confidence: 99%